PROTECTION OF MINORITY RIGHTS – A PILLAR OF A DEMOCRATIC SOCIETY (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The purpose of this paper is to contribute towards heightened awarenessabout international and comparative systems for protection of minorityrights, as a necessary element of integration in a democratic society, andtowards avoidance of its shadow - a social fragmentisation. Sublimatedbest practices are offered not as legal transplants, but as a resource forpossible solutions. The methodology encompasses legal analysis of hardand soft law applicable to minority rights, comparative analyses of bestpractices for integration of minorities from several states (Croatia,Denmark, France, Montenegro, the Netherlands, Serbia, Slovenia and the• UK) as well as analyses of responses to questionnaires by state and nonstateactors. The results are scrutinized via multi-disciplinary and humanrights approaches; with an emphasis on the civil society’s role as a crosscuttingissue. The results of the research show that the concept of a multiethnicintegrated society needs to be constantly clarified and promoted bythe Government institutions, which should underscore it as a strategicpriority among majority and minority communities in the Republic ofMacedonia; and that a cautious approach needs to be applied to avoidsocial fragmentisation on ethnic and cultural bases. The results will bedisseminated and explained at the September International Conference ofthe Law Faculty in Stip. Communication of the results includes use ofscientific repositories, press releases and use of social media.